Integrating nature-based solutions for resilient watershed management: a comparative study in urban and semi-urban watersheds of Panama and Honduras - Benegas, Laura; Ríos Ramírez, Ney; Fino Rodríguez, Líber Ilyá; Mosquera Ballejos, Carlina Felicia; Ibáñez López, Ovidio (Frontiers in Conservation Science, 2025)
This study explores the operationalization of nature-based solutions (NbS) for watershed resilience in two contrasting Latin American contexts: the Caimito watershed in Panama and the El Coyolar watershed in Honduras. The methodological framework combined spatial multi-criteria analysis using GIS tools, participatory mapping with local stakeholders, and the classification of NbS based on ecological function and governance feasibility. Results show that a total of 1,220 ha and 1,870 ha were prioritized for NbS interventions in Caimito and El Coyolar, respectively. The most feasible practices included urban green corridors, riparian buffer restoration, and agroforestry infiltration systems. Notably, Panama followed an institutionally driven planning process, whereas Honduras adopted a community-led strategy. The study highlights the importance of integrating spatial tools with local knowledge to ensure effective and context-sensitive NbS implementation.